THEORIES OF VENN DIAGRAMS (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article provides an overview and complete structure of the Venn diagram, highlighting its key characteristics, stages, and its origin as a visual model from the perspective of scholars